Integrating the Law on Environmental Protection and Management into Ecology Learning to Enhance Students Legal Awareness - Bangkit Wira Malik (Journal of Progressive Science Education, 2026)
The current global ecological crisis is often viewed as a failure of collective understanding regarding environmental legal instruments. At the secondary education level in Indonesia, there is a curricular dichotomy that separates biology from civic education, resulting in students understanding natural destruction cognitively but remaining indifferent to its juridical consequences. Previous research has extensively explored problem-based learning models; however, the majority remains limited to cognitive learning outcomes without systematically integrating legal instruments. This study aims to formulate and test the effectiveness of an ecology module integrated with crucial points of Law No. 32 of 2009 (UU PPLH) to enhance students' legal awareness. The method used is a qualitative approach with a descriptive case study design based on constructivist epistemology. Research subjects were selected through purposive sampling, involving Grade XI students and biology teachers. Data were collected through participant observation, in-depth interviews, FGDs, and documentation studies, and then analyzed using the interactive model of Miles, Huberman, and Saldana. A systematic transformation of student awareness. The integration of materials such as AMDAL (Environmental Impact Assessment) and Environmental Quality Standards successfully bridged science and legal literacy, shifting the students' paradigm from a biotic-abiotic understanding toward juridical awareness. Although initial resistance emerged due to cognitive load, the social constructivism approach was effective in transforming rigid legal texts into vibrant ethical discussions. These findings theoretically prove that legal literacy functions as a catalyst for ecological intelligence, creating ecological citizenship that is not only academically brilliant but also legally resilient in preserving the sustainability of the Earth.